2021
DOI: 10.3389/fnagi.2021.711023
|View full text |Cite
|
Sign up to set email alerts
|

Altered Patterns of Amplitude of Low-Frequency Fluctuations and Fractional Amplitude of Low-Frequency Fluctuations Between Amnestic and Vascular Mild Cognitive Impairment: An ALE-Based Comparative Meta-Analysis

Abstract: Background: Changes in the amplitude of low-frequency fluctuations (ALFF) and the fractional amplitude of low-frequency fluctuations (fALFF) have provided stronger evidence for the pathophysiology of cognitive impairment. Whether the altered patterns of ALFF and fALFF differ in amnestic cognitive impairment (aMCI) and vascular mild cognitive impairment (vMCI) is largely unknown. The purpose of this study was to explore the ALFF/fALFF changes in the two diseases and to further explore whether they contribute to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
1
6
0
Order By: Relevance
“…This study found that the sALFF in the above two brain regions of SLE patients with CI was higher than that of HCs and SLE patients without CI, respectively, suggesting that the local brain activity intensity of these two brain regions increased, which may be related to the compensation of cognitive dysfunction. Similar results have also been reported in studies of major depressive disorder (Liu et al, 2014), and amnestic CI (Zhang et al, 2021) and its specific mechanism still needs further research.…”
Section: Discussionsupporting
confidence: 86%
“…This study found that the sALFF in the above two brain regions of SLE patients with CI was higher than that of HCs and SLE patients without CI, respectively, suggesting that the local brain activity intensity of these two brain regions increased, which may be related to the compensation of cognitive dysfunction. Similar results have also been reported in studies of major depressive disorder (Liu et al, 2014), and amnestic CI (Zhang et al, 2021) and its specific mechanism still needs further research.…”
Section: Discussionsupporting
confidence: 86%
“…The ALFF method has been applied to evaluate the neural mechanisms of central disease including schizophrenia ( 21 ), epilepsy ( 22 ), mild cognitive impairment ( 23 ), and migraine ( 24 ). Besides, many studies have suggested that the ALFF of fMRI signals are closely related to the spontaneous neuronal activities such as visual cortex ( 25 ), auditory cortex ( 26 ), hippocampus ( 27 ), cingulate cortex, and postcentral gyrus ( 28 ).…”
Section: Discussionmentioning
confidence: 99%
“…While smoker/non-smoker differences have been reported in fALFF ( Wang et al, 2017 ; Tan et al, 2021 ; Weng et al, 2021 ), the interaction between fALFF, smoking status, and cognition is unknown. However, a growing literature has investigated the link between fALFF and cognitive impairment, and studies indicate increased fALFF values in the PHG among individuals with amnesic mild cognitive impairment ( Zhang et al, 2021 ). This suggests a compensatory mechanism in the early stage of cognitive impairment, and may be analogous to the reduced GMV and higher fALFF values in the smokers’ PHG that correlated with cognitive performance.…”
Section: Discussionmentioning
confidence: 99%